PENGARUH ORANG TUA DAN PELAKSANAAN SHALAT TERHADAP PERILAKU REMAJA - Al-hamdani, Rahma Zakiah; Rulitawati, Rulitawati; Jamaluddin, Jamaluddin (Raudhah - Proud To Be Professional, 2025)
this study examines the influence of parental roles and prayer practices on adolescent behavior in RT 064 RW 017, 16 Ulu Subdistrict, Seberang Ulu II District, Palembang. Adolescence is a crucial developmental phase characterized by significant physical, emotional, and social changes. During this period, family environment and religious education play a vital role in shaping an individual's moral values and behavior. This study employs a quantitative approach with a survey method, involving 30 adolescent respondents selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression analysis. The findings reveal that parental involvement significantly influences adolescent behavior, particularly in fostering discipline, responsibility, and self-control. Moreover, consistent prayer practices contribute to moral development, emotional regulation, and reducing deviant behaviors. The combined effect of parental involvement and prayer practices is found to be more impactful in shaping adolescent character compared to their individual effects. The statistical results indicate that parental guidance and prayer practices account for 87.4% of the variation in adolescent behavior, while the remaining 12.6% is influenced by other external factors. These findings highlight the importance of religious education within the family as a foundation for adolescent character development. Strengthening parental engagement in religious upbringing and encouraging consistent prayer practices can help foster positive adolescent behavior and prevent social misconduct.